2013
DOI: 10.1063/1.4819918
|View full text |Cite
|
Sign up to set email alerts
|

Deformation properties between fluid and periodic circular obstacles in polydimethylsiloxane microchannels: Experimental and numerical investigations under various conditions

Abstract: Understanding the mechanical properties of optically transparent polydimethylsiloxane (PDMS) microchannels was essential to the design of polymer-based microdevices. In this experiment, PDMS microchannels were filled with a 100 lM solution of rhodamine 6G dye at very low Reynolds numbers ($10 À3 ). The deformation of PDMS microchannels created by pressure-driven flow was investigated by fluorescence microscopy and quantified the deformation by the linear relationship between dye layer thickness and intensity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In the case where w ≫ h , as is the case of the microchannels used in Figures –, a larger deformation of the channel height was observed while the lateral deformation was negligible. This phenomenon was also described in other studies. , In general, flow resistance is larger in smaller channels. If we keep the same channel height while changing the channel width, the same volumetric flow rate is maintained.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the case where w ≫ h , as is the case of the microchannels used in Figures –, a larger deformation of the channel height was observed while the lateral deformation was negligible. This phenomenon was also described in other studies. , In general, flow resistance is larger in smaller channels. If we keep the same channel height while changing the channel width, the same volumetric flow rate is maintained.…”
Section: Resultssupporting
confidence: 86%
“…This phenomenon was also described in other studies. 18,22 In general, flow resistance is larger in smaller channels. If we keep the same channel height while changing the channel width, the same volumetric flow rate is maintained.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Shallow microuidic channels (15 mm) were fabricated by wet etching, while three deeper microuidic channels (50 mm, 100 mm and 200 mm) were fabricated by reactive ion etching (RIE) techniques for making high-aspect-ratio structures with high etching rates, straight sidewalls and complex geometries. 27 Detail information about design and chip fabrications described by Kang et al 28 The microuidic channels produced by these procedures contained fabricated microuidic channels with a measured width of 243 AE 5 mm and measured heights of 15 AE 1 mm, 50 AE 2 mm, 100 AE 5 mm and 200 AE 8 mm, respectively.…”
Section: B Experimental Design and Microchannel Fabricationmentioning
confidence: 99%
“…Schneider et al [41,44] demonstrated an adaptive fluidic PDMS-lens system with an integrated piezoelectric pumping actuator. Because PDMS membrane devices are widely used in the microfluidic field as actuator, the correlation between thickness, applied pressure, and deflection properties of PDMS membrane has been theoretically and experimentally investigated, such as PDMS channel expansion, deformation and bulging [46][47][48]. Mechanical properties of PDMS have also been investigated, including shear modulus, thickness-spin speed dependence and adhesion, and true stress-based true strain by mechanical tension testing [49][50][51].…”
Section: Introductionmentioning
confidence: 99%